COGNITIVE ABILITIES OF MALTREATED CHILDREN. Issue 1 (13th November 2014) - Viezel, Kathleen D.; Freer, Benjamin D.; Lowell, Ari; Castillo, Jenean A.; Viezel, Kathleen D.; Davis, Andrew S.
<x xml:space="preserve">Abstract</x> School psychologists should be aware of developmental risk factors for children who have been abused or neglected. The present study used the Wechsler Intelligence Scale for Children, Fourth Edition to examine the cognitive abilities of 120 children in foster care subsequent to maltreatment. Results indicated that, compared to a demographically matched comparison group, the children who experienced maltreatment had lower full‐scale intelligence quotients and profile analysis uncovered potential strengths and weaknesses. The perceptual reasoning and working memory abilities of the maltreated group were commensurate with those of the comparison group. Conversely, the overall verbal comprehension and processing speed abilities of the maltreated children were significantly lower than the control group. At the subtest level, the children who experienced maltreatment had lower Vocabulary, Comprehension, and Coding scores. To address the paucity of information in the literature about children who have been neglected, follow‐up analyses were conducted for children who were neglected, but not abused. Results indicated a similar, but not identical, pattern of findings. Implications and recommendations for school psychologists are discussed.